Observations of thermospheric neutral winds within the polar cusp and the auroral oval using a Doppler imaging system (DIS). - Henriksen, K.; Rees, D.; Smith, R.W.; Signernes, F.; Brandstrom, U.; Harris, M.; Maskall, G. (European Geophysical Society, 1998)
Two Doppler imaging systems (DIS) or wide-field imaging Fabry-Perot interferometers (FPI), have recently been commissioned, one at the Auroral Station, Adventdalen, Longyearbyen, Svalbard, and the second at the IRF, Kiruna, Sweden. These instruments can provide wide-field (600 * 800 km) images of neutral wind flows in the upper thermosphere, by measuring the Doppler shift of the atomic oxygen forbidden near 630 nm, which is emitted from an altitude of approximately 240 km. From the instrument in Svalbard, at mid-winter, it is possible to observe the dayside polar cusp and the polar cap throughout the entire day, whereas from Kiruna, the night-time auroral oval is observable during the hours of darkness. Measurements of thermospheric dynamics from the DIS can be used in conjunction with observations of ionospheric plasma flows and thermal plasma densities by the EISCAT-Svalbard radar (ESR) and by EISCAT, along with other complementary observations by co-located instruments such as the auroral large-scale imaging system (ALIS). Such combined data sets will allow a wide range of scientific studies to be performed concerning the dynamical response of the thermosphere and ionosphere, and the important energetic and momentum exchange processes resulting from their complex interactions. These processes are particularly important in the immediate vicinity of the polar cusp and within the auroral oval. Early results from Svalbard in late 1995 will be discussed. The DIS in Kiruna observed two interesting geomagnetic disturbances in early 1997, the minor geomagnetic storm of 10, 11 January, and the disturbed period from 7–10 February. During these events, the thermospheric wind response showed some interesting departures from the average behaviour, which we attribute to the result of strong and variable Lorenz forcing (ion drag) and Joule and particle heating during these geomagnetic disturbances.